PERAN FINANCIAL LEVERAGE, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP INCOME SMOOTHING (Media Riset Akuntansi, 2022)
Profitability for income smoothing. The data used are secondary data used in the form of reports audit of mining companies sector that registered on the Stock Exchange since 2012- 2016. The sample obtained by the method purposive sampling with 170 samples late. This research uses multiple linear regression analysis as a hypothesis test with the software application Eviews V.8 According to the result of research that had been on manufacturing companies in mining that registered on the Stock Exchange, we can be concludes that financial leverage and profitability affect on income smoothing, while the size of the company does not affect on income smoothing. Variable financial leverage allegedly affecting because high leverage also have a high of risk.. Variable size of the company is thought to have no effect because of the differences in government regulations of developed countries with developing country regulations. The profitability variable allegedly affecting because investors pay attention to profitability, so management is motivated to beautify their financial statements.